2021
DOI: 10.3389/fmicb.2021.708182
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-Resistant Escherichia coli Strains and Their Plasmids in People, Poultry, and Chicken Meat in Laos

Abstract: Antimicrobial resistant (AMR) Enterobacterales are widely distributed among the healthy population of the Indochinese peninsula, including Laos. However, the local reservoir of these pathogens are currently not known and possible sources such as agricultural settings and food have rarely been analyzed. In this work, we investigated the extended-spectrum cephalosporin- (ESC-) and colistin-resistant Escherichia coli strains (CST-R-Ec) isolated from the gut of local people, feces of poultry, and from chicken meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
3
20
1
Order By: Relevance
“…Also, an almost similar overall prevalence of AMR was observed in ExPEC (caeca/retail butcher shops/ urban = 76.9%; faeces/poultry farms/rural areas = 78.6%) or non-ExPEC isolates (caeca/retail butcher shops/ urban = 74.9%; faeces/poultry farms/rural areas = 73.4%) (Supporting Information Tables S1 and S2). Interestingly, our results are strongly in contrast to the results of previous studies in which AMR prevalence in E. coli isolates varied according to the poultry associated-sample sources (chicken faecal or meat) or environments (poultry et al, 2001;Moser et al, 2021). There is no clear explanation for this, but it might be related to variations in antimicrobial uses in poultry, poultry environments/sampling and geographical regions, and further studies are needed to confirm the present findings.…”
Section: Single Drug Resistancecontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, an almost similar overall prevalence of AMR was observed in ExPEC (caeca/retail butcher shops/ urban = 76.9%; faeces/poultry farms/rural areas = 78.6%) or non-ExPEC isolates (caeca/retail butcher shops/ urban = 74.9%; faeces/poultry farms/rural areas = 73.4%) (Supporting Information Tables S1 and S2). Interestingly, our results are strongly in contrast to the results of previous studies in which AMR prevalence in E. coli isolates varied according to the poultry associated-sample sources (chicken faecal or meat) or environments (poultry et al, 2001;Moser et al, 2021). There is no clear explanation for this, but it might be related to variations in antimicrobial uses in poultry, poultry environments/sampling and geographical regions, and further studies are needed to confirm the present findings.…”
Section: Single Drug Resistancecontrasting
confidence: 99%
“…Interestingly, our results are strongly in contrast to the results of previous studies in which AMR prevalence in E . coli isolates varied according to the poultry associated‐sample sources (chicken faecal or meat) or environments (poultry farms and poultry slaughterers) (Van den Bogaard et al ., 2001; Moser et al ., 2021). There is no clear explanation for this, but it might be related to variations in antimicrobial uses in poultry, poultry environments/sampling and geographical regions, and further studies are needed to confirm the present findings.…”
Section: Resultsmentioning
confidence: 99%
“…However, for some countries, the reported numbers were much higher, with low-income countries usually showing a higher prevalence. For instance, studies from Tanzania (2018), Laos (2018), and Thailand (2010) reported rates of ESBL-Ent carriage in the healthy population as high as 91.5%, 70%, and 69.3%, respectively [88][89][90]. Though in high-income Asian countries such as Japan, the prevalence for ESBL-Ec in 2011-2012 (8.5%) was comparable to those reported for European countries (e.g., 7.1% in Switzerland in 2013-2016) [57,91].…”
Section: Community Settingmentioning
confidence: 99%
“…During 2016-2019, the prevalence of COL-R-Ent carriage among healthy people ranged from 2 to 3% in studies conducted in Taiwan, Spain (considering health-care workers, HCWs), and South Africa (considering children), while it was 15% in two studies that analyzed healthy Chinese and Laotian people in 2016 and 2018-2019, respectively [89,[99][100][101][102]. In contrast, a study from Bolivia (2016) and one from Vietnam (2017-2018) reported a wide dissemination of COL-R bacteria in the healthy community with rates of 38.3% and 70.4%, respectively [103,104].…”
Section: Community Settingmentioning
confidence: 99%
“…The data could serve as a baseline for future qualitative AMR risk assessment frameworks [ 54 ]. A study of AMR clustering among farmworkers, chickens, and farm environments [ 55 ] integrating novel genomic techniques [ 56 ] could provide detailed insight into AMR transmission in foodborne pathogens and exposure risks in poultry farms in the region. Although it was not measured, these results hint at the possible work-related risk of exposure to highly resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%